Hepatitis B reactivation and immune check point inhibitors. Issue 4 (April 2021) - Godbert, Benoit; Petitpain, Nadine; Lopez, Anthony; Nisse, Yann-Eric; Gillet, Pierre
Abstract: Background: Liver toxicity during immune checkpoint inhibitor treatment is mostly due to immune mediated hepatitis. Viral hepatitis, as well as auto-immune or metabolic hepatitis, are considered as exclusion criteria for ICI induced immune hepatitis diagnosis. However, considering the high prevalence of viral hepatitis B infection and the increasing prescription of immune checkpoint inhibitors, their use in patients with HBV chronic viral infection may be common, even more if patients are treated for hepatocellular carcinoma. Few clinical studies directly deal with the risk of HBV reactivation during ICI therapy and real-life data is currently based on five reported cases of HBV reactivation, one with fatal outcome. In this review, we summarize the current available clinical information about HBV reactivation risk during ICI treatment, its hypothetic mechanism, and propose practical recommendations about verifying and monitoring HBV status throughout the treatment.